2022
DOI: 10.3389/feduc.2022.975105
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking pre-service teachers’ beliefs and reasoning about student ability, sources of teaching knowledge, and teacher-efficacy: A scenario-based approach

Abstract: The beliefs teachers hold may provide information about their more or less evidence-informed reasoning about educational issues. However, gaining a clear picture of teachers’ beliefs has proven difficult. A promising line of inquiry uses scenario-based approaches to assess teachers’ enacted beliefs. Accordingly, we assessed 75 Norwegian pre-service teachers’ beliefs about student ability, sources of teaching knowledge, and teacher efficacy by analyzing their written responses to authentic classroom scenarios, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, this direct approach has limited value when it comes to measuring deep-set, sometimes unconscious beliefs. Implicit or qualitative methods would be a fruitful addition (see Ferguson & Bråten, 2022; Lüftenegger & Chen, 2017). Future research should also relate the dependent variables more closely to actual behavior, for example, by measuring how teachers search for and use scientific data or the extent to which they use student feedback to improve their teaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, this direct approach has limited value when it comes to measuring deep-set, sometimes unconscious beliefs. Implicit or qualitative methods would be a fruitful addition (see Ferguson & Bråten, 2022; Lüftenegger & Chen, 2017). Future research should also relate the dependent variables more closely to actual behavior, for example, by measuring how teachers search for and use scientific data or the extent to which they use student feedback to improve their teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Now the more pressing concern is that teachers who are considered digital natives often lack the training to formally integrate digital tools into their teaching (Colwell et al, 2020; Lei, 2009). Indeed, PSTs may not be comfortable integrating digital texts into their instruction due to their beliefs about student ability and their own teaching efficacy (Ferguson & Bråten, 2022), beliefs about the value of digital text as compared to print text (McKnight, 2021), and their personal educational philosophies (Alanoglu et al, 2022). This study indicates that the use of a structured and phased planning approach may alleviate PST hesitations about integrating disciplinary practices and digital texts, providing a promising approach to PST training in digital tool integration.…”
Section: Discussionmentioning
confidence: 99%
“…This resembles the findings of Menz et al (2021), who found that pre-service teachers' beliefs were often based on anecdotal evidence, namely personal experiences and narratives from other people, rather than scientific evidence. Similarly, Ferguson and Bråten (2022) found that pre-service teachers (N = 75) relied on informal knowledge sources rather than educational research in a scenario-based task that required pedagogical decision-making. Further, List et al (2022) found that less than half (44%) of pre-service teachers mentioned the need to consider source bias (e.g., author reliability, commercial intent), and only 8% mentioned the need to consider content bias (benefits and limitations) when evaluating educational app reviews.…”
Section: Previous Research On Pre-service Teachers' Credibility Evalu...mentioning
confidence: 99%